Les cadrages de l’agriculture au Conservatoire du littoral - Alban Landré (VertigO, 2023)
The French Conservatoire du littoral was created in 1975 to bring a balance between the building and the protection of the shores. The mission of this national public administrative agency is to buy coastal plots to protect and manage landscapes and natural habitats. Among the purchased plots, around 15% are agricultural land. But can the landscape and conservation missions of the Conservatoire du littoral cope with productive farming activities ? To manage certain habitats, the Conservatoire du littoral considers certain agricultural activities as necessary. It is the case of grasslands that require management by mowing and/or grazing. Other farming activities are sometimes tolerated or encouraged on Conservatoire du littoral lands. Contract specifications with ecological conditions are negociated with farmers to frame the practices. The article goes through the history of the preference for grasslands at the Conservatoire du littoral, while also presenting the other types of agricultural activities encountered on the agency’s land. The aim is to present the series of questions and knowledge that led to the formulation and current development of the principles of action in agriculture at the Conservatoire du littoral.